Tekanan, Kesempatan, dan Rasionalisasi Pemicu Tindakan Kecurangan (Fraud) pada Perusahaan - Kadek Rai Suwena (Jurnal Ilmiah Akuntansi, 2021)
The purpose of this study is to determine the effect of pressure, opportunity, and rationalization on fraud. The research design is causal quantitative research. The sample of this study was determined by purposive sampling technique by 42 respondents. Data collection methods used were questionnaire and interview. Data analysis techniques using multiple linear regression analysis. As for the results of this study show that (1) the pressure, opportunity, and ratinalization have a positive and significant effect on fraud. (2) Pressure has a positive and significant effect on fraud. (3) The opportunity to have a positive and significant effect on fraud. (4) Rationalization has a positive and significant effect on fraud.